Activating mutations in the MAP‐kinase pathway define non‐ossifying fibroma of bone. Issue 1 (24th January 2019) - Baumhoer, Daniel; Kovac, Michal; Sperveslage, Jan; Ameline, Baptiste; Strobl, Anna‐Christina; Krause, Arthur; Trautmann, Marcel; Wardelmann, Eva; Nathrath, Michaela; Höller, Sylvia; Hardes, Jendrik; Gosheger, Georg; et al.
Abstract: Non‐ossifying fibroma (NOF), which occasionally results in pathologic fracture, is considered the most common benign and self‐limiting lesion of the growing skeleton. By DNA sequencing we have identified hotspot KRAS, FGFR1 and NF1 mutations in 48 of 59 patients (81.4%) with NOF, at allele frequencies ranging from 0.04 to 0.61. Our findings define NOF as a genetically driven neoplasm caused in most cases by activated MAP‐kinase signalling. Interestingly, this driving force either diminishes over time or at least is not sufficient to prevent autonomous regression and resolution. Beyond its contribution to a better understanding of the molecular pathogenesis of NOF, this study adds another benign lesion to the spectrum of KRAS ‐ and MAP‐kinase signalling‐driven tumours. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.